The neuroscience basis and educational interventions of mathematical cognitive impairment and anxiety: a systematic literature review - Yu, Hao (Frontiers in Psychology, 2023)
This systematic literature review aims to explore the neuroscience basis and educational interventions of mathematical cognitive impairment and anxiety. Mathematics, as a universal foundational subject, plays a crucial role in various fields such as education and neuroscience. Understanding the cognitive processes and mechanisms involved in mathematical cognition is essential for optimizing teaching methods, improving student learning experiences, and enhancing overall educational outcomes. However, mathematical cognitive impairment and anxiety are prevalent and severe issues hindering individual mathematical learning and application. To investigate the potential neuroscience basis and effective educational interventions for these problems, researchers have conducted extensive studies using various methods, including behavioral experiments and neuroimaging techniques. This review has screened 62 research articles that meet the ESSA evidence levels from multiple databases, identifying key themes and delving into the neuroscience basis of mathematical cognitive impairment and anxiety and their impact on educational practices. Additionally, it will summarize and analyze the shortcomings of existing research, aiming to find new directions and possible improvement strategies for future research.